Urban Heat Island and Park Cool Island Intensities in the Coastal City of Aracaju, North-Eastern Brazil - Anjos, Max (2017)
In this study, an evaluation of the Urban Heat Island (UHI) and Park Cool Island (PCI) intensities in Aracaju, North-Eastern Brazil, was performed. The basis of our evaluation is a 2-year dataset from the urban climatological network installed with the principles and concepts defined for urban areas related to climatic scales, sitting and exposure, urban morphology, and metadata. The current findings update UHI intensities in Aracaju refuting the trend registered in previous studies. On average, the UHI was more intense in the cool season (1.3 °C) than in hot season (0.5 °C), which was caused by wind speed decrease. In relation to the PCI, mitigation of high air temperatures of 1.5–2 °C on average was registered in the city. However, the urban park is not always cooler than the surrounding built environment. Consistent long-term monitoring in the cities is very important to provide more accurate climatic information about the UHI and PCI to be applied in urban planning properly, e.g., to provide pleasant thermal comfort in urban spaces.